Peneraapan Model HOT Fit pada Evaluasi Kinerja Human Resources Information System (HRIS) di KPKNL Palembang - Bunga Pertiwi; Evi Yulianingsih (Jurnal Pengembangan Sistem Informasi dan Informatika, 2020)
Human Resources Information System (HRIS) is a system that functions to manage all information related to human resources in an institution. This study aims to evaluate and assess the current system and to see the relationship of the variables in the HOT Fit method to HRIS users in KPKNL Palembang. There are three independent variables in this model, each variable has its own sub-variables. Human variables have sub-variables: System Users (PS) and User Satisfaction (KP), Organization Variables have sub-variables: Organizational Structure (SO) and Organizational Environment (LO), and Technology Variables have sub-variables: System Quality (KS), Quality Information (IC), and Service Quality (KL), In addition to the independent variable of this study there are also dependent variables, namely Net Benefit. From these variables, it will be the focus of this research. In this study the authors will use quantitative descriptive research methods by observing, interviewing, and distributing questionnaires. This study uses a Likert scale in measuring employee attitudes and perceptions of the product to be assessed. Because there are only 38 Civil Servants (PNS), all of them will be taken as samples. From this study, the authors hope that the agency can use it as a reference in perfecting the current system.